2011
DOI: 10.1002/marc.201100255
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Detection and Removal of Mercury Ions in Aqueous Solution with Fluorescent Conjugated Polymer‐Based Sensor Ensemble

Abstract: A water-soluble, sulfur-containing fluorescent conjugated polymer exhibits a visible fluorescence color change for detection of mercury in the presence of thymine. A new concept provides the design of a sensor ensemble using a simple combination method. This strategy avoids the need for complicated design and synthesis of a recognition group, eliminating the tedious synthetic efforts for the preparation of a sensor material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…That is, the addition of Hg 2+ distract I -from the PFTD/Icomplex due to the stronger association strength between them, the heavy atom effect brought by I -was thus ruined and the fluorescence recovered accordingly [27-30, 33, 34]. It is well known that there is also high affinity between Hg 2+ and sulfur, and several fluorescence turn-off mode, CPs-based Hg 2+ probes [18][19][20][21][22] have been designed by taking advantage of such typical Pearson's soft acids and bases interaction [38]. The result in our recent work about thymine-decorated, fluorene and DBT based CPs also revealed that the fluorescence of DBT and DBT-containing polymers will be quenched by the addition of Hg 2+ [39].…”
Section: Optical Response Of Pftd/i -Assembly Toward Hg 2+mentioning
confidence: 97%
See 1 more Smart Citation
“…That is, the addition of Hg 2+ distract I -from the PFTD/Icomplex due to the stronger association strength between them, the heavy atom effect brought by I -was thus ruined and the fluorescence recovered accordingly [27-30, 33, 34]. It is well known that there is also high affinity between Hg 2+ and sulfur, and several fluorescence turn-off mode, CPs-based Hg 2+ probes [18][19][20][21][22] have been designed by taking advantage of such typical Pearson's soft acids and bases interaction [38]. The result in our recent work about thymine-decorated, fluorene and DBT based CPs also revealed that the fluorescence of DBT and DBT-containing polymers will be quenched by the addition of Hg 2+ [39].…”
Section: Optical Response Of Pftd/i -Assembly Toward Hg 2+mentioning
confidence: 97%
“…The common designing thought of CPs-based Hg 2+ probes were based on the strong interaction between Hg 2+ and sulfur (S) atoms embedded in polymers' structures [11,[18][19][20][21][22]. The working manner of the majority of these probes were depend on the fluorescence 'turn-off' mechanism, that is, the fluorescence of CPs was quenched with the addition of Hg 2+ [18][19][20][21][22]. As compared to turn-off probes, fluorescence enhancing (turn-on) probes displayed superiority from the view-point of ease in detection (the optical signals were strengthened during the detection) and anti-interference [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, fluorescent chemical sensors are elegant alternative to the traditional analytical instruments. Currently, a great number of efforts have been made to develop more fluorescent sensors for the detection of mercury and mercuric salts with sensitivity and selectivity [4,[11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Optical probes have been widely developed for detecting analytes because of their high sensitivity, low cost, easy detection, and reusable properties in some cases 14–17. Thus, a series of small molecules,18, 19 polymers,20–22 DNA,23, 24 and nanomaterials25, 26 based optical sensors for Hg 2+ have been successfully synthesized.…”
Section: Introductionmentioning
confidence: 99%
“…Ren and Xu41 used a combination of oligonucleotides, DNA intercalators, and CP for the turn‐on detection of Hg 2+ by combining the effect of the specific binding between Hg 2+ and T and the optical amplification properties of CPs. Lee et al22 took advantage of the interactions among sulfur, Hg 2+ , and T to probe Hg 2+ with S‐containing CPs as optical reporters and bisthymine as shackles. To obtain chemically stable CP/T systems, polythiophene and poly( para ‐phenylene)‐based CPs with Ts covalently bonded on the side chains have been successfully synthesized by the research groups of Wang et al42 and Li et al,43 respectively.…”
Section: Introductionmentioning
confidence: 99%